2011
DOI: 10.1093/cercor/bhr176
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preterm Birth on Thalamic and Cortical Development

Abstract: Preterm birth is a leading cause of cognitive impairment in childhood and is associated with cerebral gray and white matter abnormalities. Using multimodal image analysis, we tested the hypothesis that altered thalamic development is an important component of preterm brain injury and is associated with other macro- and microstructural alterations. T1- and T2-weighted magnetic resonance images and 15-direction diffusion tensor images were acquired from 71 preterm infants at term-equivalent age. Deformation-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
247
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(282 citation statements)
references
References 62 publications
28
247
2
2
Order By: Relevance
“…In previous studies of similar cohorts, we and others have observed decreased frontotemporal volume, increased thalamic diffusivity, and decreased FA in the central white matter with increasing prematurity 7, 10, 12, 35. Here, we show these changes are coupled, independent of age at scan and total intracranial volume, and exacerbated by comorbid markers of neonatal sickness.…”
Section: Discussionsupporting
confidence: 78%
“…In previous studies of similar cohorts, we and others have observed decreased frontotemporal volume, increased thalamic diffusivity, and decreased FA in the central white matter with increasing prematurity 7, 10, 12, 35. Here, we show these changes are coupled, independent of age at scan and total intracranial volume, and exacerbated by comorbid markers of neonatal sickness.…”
Section: Discussionsupporting
confidence: 78%
“…Besides the event of preterm birth itself posing substantial risk to the establishment of healthy and fully operational brain network organization, prematurity is frequently accompanied by postnatal illness that may amplify the detrimental effects on early brain wiring. Not surprisingly, preterm birth is associated with impaired brain development reflected in reduced brain volumes, diminished cortical gyrification and delayed maturation of gray and white matter structures (Ball et al, 2012;Keunen et al, 2012;Rathbone et al, 2011;Shimony et al, 2016;Volpe, 2009). These deficits are also present in the absence of focal brain injury and have been noted to persist through childhood (Counsell et al, 2008;FischigĂłmez et al, 2015;Monson et al, 2016).…”
Section: Preterm Birthmentioning
confidence: 99%
“…The thalamus and basal ganglia are known to mediate motor processes and have been found to be vulnerable to injury in infants (7,39); which could partially explain impaired motor and cognitive function associated with preterm birth. In preterm compared to term infants, decreased thalamus volume (39) and impaired thalamocortical connectivity (40) have been reported.…”
Section: Thalamus and Globus Pallidusmentioning
confidence: 99%